The Effect of Salinity on the Effectiveness of CO2 Injection in the CO2 Storage Project in Bunter Field - Fitri, Syahri Fani (Journal of Petroleum and Geothermal Technology, 2025)
The increase in CO₂ concentration in the atmosphere has contributed to global warming. Reducing CO₂ emissions can be achieved through Carbon Capture Storage (CCS) projects, optimized by selecting appropriate formation water salinity for CO₂ injection. High salinity can impede CO₂ movement and cause mineral deposits, potentially clogging rock pores and reducing CO₂ solubility. This paper aims to analyze the impact of salt concentration in brine on CO₂ solubility and storage capacity in saline aquifers. In this study, a sensitivity simulation was conducted on an existing saline aquifer dataset to analyze the effects of varying formation water salinity using a CO₂ sequestration method with a reservoir simulator. Simulation results showed that different salinity levels in formation water yield varying CO₂ solubility rates; for instance, in a formation with water salinity of 1000 ppm, CO₂ solubility increased with a storage capacity of 910.283 MMscf, whereas at 100.000 ppm salinity, CO₂ solubility decreased, and the CO₂ storage capacity was slightly lower at 652.440 MMscf. Formations with lower salinity are considered more ideal for CCS projects as they can maintain higher CO₂ storage capacity and long-term stability. This study is expected to provide additional insights into enhancing the CO₂ solubility mechanism in saline aquifers.